The Effect of the Covid-19 Pandemic on Financial Profitability at the Balo' Ta Savings and Loan Cooperative - Pangraran, Fisca Mawa; Haliah; Nirwana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to ascertain and evaluate the profitability of financial statements pertaining to the Balo ‘Ta Savings and Loan Cooperative for the period 2019-2021, both prior to and throughout the COVID-19 pandemic. Research findings and data analysis indicate that the financial profitability of the Balo ‘Ta savings and loan cooperative has fluctuated between increasing and decreasing in response to the COVID-19 pandemic. The profitability of cooperatives is assessed through the utilization of return on equity, return on assets, net profit margin, and operating profit margin metrics. In contrast, the gross profit margin exhibited a decline over the course of 2019 to 2021.